Penerapan Teknologi dalam Peningkatan Motivasi dan Keterlibatan Siswa Kelas VI SDN Barengkok 1 - Lutfiyani, Siti; Sinuraya, Putri Yohana; Anggraini, Resti Wicitra; Enov, Adelia; Ulailiah, Sipa (Universitas PGRI Semarang, 2023)
In the 21st century, technology has an increasingly important role, especially as a trigger for student learning motivation so that they have learning skills. Skills to use technology help to get information faster and improve life skills as a working capital and educators also easily develop learning materials. Technology is also useful for students in finding, collecting, documenting, processing and transferring back teaching materials as needed. Seeing the current reality where there are still many students who are low in learning motivation will certainly affect their learning outcomes or achievements. The purpose of this research is to find out how much influence the use of technology has on students' learning motivation at SDN Barengkok 1. This research was conducted on November 16-20 2021 with the number of samples used as many as 27 grade VI students in the odd semester of the 2021/2022 class. This study uses a quantitative approach and survey research methods. The stages of the research are observation of research locations, preparation of questionnaires, distribution of questionnaires, giving learning methods to teachers, data collection, processing of research results, analysis of research results and discussion results. The results showed that after the use of technology there was an increase in the share never to 0%, often from 48% to 26% and always from 37% to 70%, while the share sometimes remained the same at 4%. Student involvement in learning also increased by 2%. So, it can be concluded that if technology is used in teaching and learning activities, the motivation and involvement of students will increase.